Examining Teaming and Tier 2 and 3 Practices Within a PBIS Framework. (January 2023) - Nese, Rhonda N. T.; Kittelman, Angus; Strickland-Cohen, M. Kathleen; McIntosh, Kent
One core feature of Positive Behavioral Interventions and Support (PBIS) is a systems-level teaming process for coordinating staff implementation of evidence-based practices and monitoring student progress across all three tiers. Prior research has shown schools that report regular teaming and team-based data use are more likely to successfully adopt and sustain implementation of multi-tiered systems of behavior support. However, more research is currently needed to better understand the various teaming configurations, structures, and practices commonly used by PBIS teams in typical schools, particularly at advanced tiers. For the current study, members of school and district PBIS teams representing 718 U.S. schools were surveyed to better understand (a) teaming configurations and practices currently being used in schools implementing PBIS and (b) common interventions that PBIS teams report implementing at Tiers 2 and 3. Survey findings are discussed, along with implications of those results for future research and practice in applied settings.